2010
DOI: 10.1007/s00181-010-0448-6
|View full text |Cite
|
Sign up to set email alerts
|

Network externalities in consumer spending on lottery games: evidence from Spain

Abstract: We use data from two nationally representative Spanish surveys in 2005 and 2006 to investigate spending on lottery games. Estimates from Tobit and double hurdle models of participation in lottery markets and spending on lottery tickets find that frequent participation in one game is not associated with an increased or decreased probability of participating in other games, but is associated with increased spending on other games. Consumer spending on different lottery games exhibits inter-related consumption de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This is not unexpected at all, but actually consistent with existing research. 13,15 When addressing interdependencies and time preferences for smoking, drinking, and gambling, research founds that the more education, the less time preference for gambling and therefore likelihood of addiction. 8 In fact, it is concluded that “governments might consider education as an effective countermeasure for stopping addictions.” 8…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not unexpected at all, but actually consistent with existing research. 13,15 When addressing interdependencies and time preferences for smoking, drinking, and gambling, research founds that the more education, the less time preference for gambling and therefore likelihood of addiction. 8 In fact, it is concluded that “governments might consider education as an effective countermeasure for stopping addictions.” 8…”
Section: Resultsmentioning
confidence: 99%
“…Further detailed information about participation in the previously mentioned different gambling activities and the survey sampling methodology can be found in the technical report of the study. 15…”
Section: Data and Variablesmentioning
confidence: 99%
“…Several studies have looked at the relationships among different types of lottery products, focusing either on revenues from particular lottery games or aggregate government lottery revenues . For example, using telephone survey data from Spain, Humphreys and Perez () found that different types of lottery products appear to be complementary with respect to total sales. In particular, they found that participation in one type of lottery is linked to increased expenditure on other lottery products.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…As the popularity of lottery games has grown steadily, understanding consumer demand for the products has received considerable attention from researchers of various scholarly perspectives, such as economists, psychologists, and sociologists. The empirical literature in this area has focused on such research questions as “Why do people play lottery games?” “Who are they purchasing lottery tickets?” and “How do lottery features (for example the prize structure) affect the demand for lottery tickets?” Mao and Zhang (2013) categorized previous studies into three groups, including those related to product attribute variables, such as effective price, jackpot, prize structure, and probability of winning (Deboer, 1990; Forrest et al , 2002; García and Rodríguez, 2007; Garrett and Sobel, 2004; Humphreys and Perez, 2012; Matheson, 2001; Scoggins, 1995; Scott and Gulley, 1995; Shapira and Venezia, 1992), those related to consumer characteristic variables, such as income, gender, age, education, religion, and ethnicity (Nwigwe et al , 2012; Clotfelter and Cook, 1987; Crowley et al , 2012; Felsher et al , 2003; Herring and Bledsoe, 1994; Walker et al , 2006), and those related to marketing variables, such as venue accessibility (Hing and Haw, 2009; Shiller, 2000; Sleight et al , 2002; Welte et al , 2004), cross-border competition (Kitchen and Powells, 1991), and product substitution (Forrest et al , 2004; Forrest and McHale, 2007; Garrett and Marsh, 2002; Grote and Matheson, 2006; Guryan and Kearney, 2008; Humphreys and Perez, 2012; Lin and Lai, 2006; Trousdale and Dunn, 2014), take-out rate (Clotfelter and Cook, 1989; DeBoer, 1986; Mikesell, 1987; Vasche, 1985), and social responsibility marketing (Li et al , 2011).…”
Section: Introductionmentioning
confidence: 99%